Ethnic and religious identities of Chinese-Kristen/Katolik schoolgirls in a high school setting: An ethnolinguistic case study - Ikasari, Wipsar Siwi Dona; Widodo, Pratomo; Suryaman, Maman; Ashadi, Ashadi (LITERA, 2024)
The interplay of gender, ethnicity, and religious identifications plays an important role in the daily lives of Indonesians (Bertrand, 2004; Hoon, 2013; Ikasari, 2009; 2020; Suryadinata, et al., 2003).This study looks at Indonesian young girls' ways of being ethnic and religious, in relation to their schooling experiences to determine the manner in which these schoolgirls construct their ethnic and religious identities in the school environment. It is expected to add on to previous and current studies of women/girls in the Indonesian context. Located in a public secondary co-educational school in Yogyakarta, the study involved three schoolgirls from the Chinese ethnicity and Christian religion. Drawing on cultural studies and feminism of identity and difference as the theoretical and methodological framework, the study attempted to explore Indonesian schoolgirls' experiences and constructions of ethnicity and religion. This research is a qualitative descriptive study using case study as its method. The research data were collected from free-format, short autobiography essays written by the participants, individual and group interviews, and observation as well as online communications. Data analyses were initially carried out through data coding as determined by the research questions. The findings show that, first, the three ethnic-religious groups in this study namely the Chinese-Kristiani girls set up binaries of their essentialised understandings of being ethnic and religious members. Second, there are different ways of learning shaped by their ethnicity and religion. These two identities, in turn, shape their learning outcomes within and beyond their schooling site.